2011
DOI: 10.1258/jhsrp.2010.010084
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patient choice of provider on equity: Analysis of a patient survey

Abstract: More educated, affluent patients were no more likely to be offered a choice than other population groups, but there does appear to be a social gradient in who chose to travel beyond the local area for treatment. If these results were replicated across England, there is at least the potential risk that when local hospitals are failing, patient choice could result in inequitable access to high quality care, rather than enhancing equity as the policy's architects had hoped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 16 publications
(19 reference statements)
6
40
1
7
Order By: Relevance
“…Research shows that few patients actively choose their healthcare provider [16,30,41,47-49,64]. For example, Schwartz (2005) found that only ten per cent of patients seriously considered an alternative to their local hospital when undergoing surgery [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that few patients actively choose their healthcare provider [16,30,41,47-49,64]. For example, Schwartz (2005) found that only ten per cent of patients seriously considered an alternative to their local hospital when undergoing surgery [49].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, patients rely on their GP to choose for them [2,41,49,67,70,79,80] or go to the nearest provider [27,59,81]. Furthermore, patients rely on their previous healthcare experiences when deciding where to receive care [25,46,47,49]. This seems to apply to both Europe and the USA (for those patients who can choose).…”
Section: Resultsmentioning
confidence: 99%
“…Their justification for conducting a binary choice experiment rather than a full DCE was that the choice being made is much simpler for participants to understand for a binary choice experiment, suggesting that it might be possible to see more evidence of tradeoffs between different characteristics. [29] use a full DCE administered as a postal survey to determine how patient characteristics might affect the decisions made; in particular a patient's education and social status are considered. This followed on from a large DCE carried out in the UK and described in [9].…”
Section: Background: Discrete Choice Modellingmentioning
confidence: 99%
“…Utilisation is a function of access to health services and is affected by geographical accessibility, alongside many other factors [3-9]. In low income countries, such as those of the African continent where the burden of ill health is greatest [10-14], adequate information on the location of populations, health services, facility workload, patient addresses and socio-demographic characteristics are rarely available to develop high resolution utilisation models nationally [15,16].…”
Section: Introductionmentioning
confidence: 99%